Passivation Using Molecular Halides Increases Quantum Dot Solar Cell Performance. Issue 2 (18th November 2015) - Lan, Xinzheng; Voznyy, Oleksandr; Kiani, Amirreza; García de Arquer, F. Pelayo; Abbas, Abdullah Saud; Kim, Gi‐Hwan; Liu, Mengxia; Yang, Zhenyu; Walters, Grant; Xu, Jixian; Yuan, Mingjian; Ning, Zhijun; et al.
Abstract : A solution‐based passivation scheme is developed featuring the use of molecular iodine and PbS colloidal quantum dots (CQDs). The improved passivation translates into a longer carrier diffusion length in the solid film. This allows thicker solar‐cell devices to be built while preserving efficient charge collection, leading to a certified power conversion efficiency of 9.9%, which is a new record in CQD solar cells.